The Development of a Mobile Application for a Reward-Based Student-Lecturer Appointment Using Ethereum Blockchain and Smart Contracts - Ahmad Shokkri, Muhamad Syamim Irfan; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2023)
WeMeet DApps is an application that utilizes Blockchain technology and Smart Contracts to facilitate student-lecturer appointments and provide rewards. The primary objective of this application is to foster connections between UTHM students and their respective teachers. Furthermore, it offers the possibility of granting prizes to students who demonstrate a strong commitment to their academic pursuits. The UTHM Token, valued at 1 Ringgit Malaysia (RM) per unit, is awarded as a reward. By utilizing the smart contract address, all transactions involving this token can be effectively monitored and tracked. The application is developed using an object-oriented approach, employing the Prototype model to ensure compatibility with the system development process. The software used for development is Visual Studio Code, a code editor, which is based on Android Technology. Additionally, a MySQL server is employed to store data in a database. Ultimately, the anticipated outcome of WeMeet DApps is to provide optimal utilization and benefits to UTHM students and lecturers alike.